1995
DOI: 10.1021/jm00021a017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of efficient pentapeptide substrates for the tyrosine kinase pp60c-src

Abstract: The development of inhibitors of protein tyrosine kinases (PTKs) is a promising approach to obtaining new therapeutic agents for a variety of diseases, particularly cancer. However, the discovery of peptide-based inhibitors has been hindered by the lack of small peptide substrate sequences (i.e. five residues or less) with which a variety of inhibitor designs could be readily evaluated by replacing the Tyr with natural and unnatural amino acids. These prototypical small peptide inhibitors could then form the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…The related PTK c-Src strongly required glutamic acid in position −3, isoleucine, leucine or valine in position −1, tryptophan or glycine in position +1, and one of the aromatic residues phenylalanine, tryptophan or tyrosine in position +3, The resulting consensus substrate E-X-L/I-Y-W/G-X-F/W-X resembles the findings from the chemical library approach, where the best substrates for both v-Src and c-Src appeared to be -E/D-E-E-I-Y-G-E-F . The K m of the corresponding peptide A-E-E-E-I-Y-G-E-F-E-A-K-K-K was reported to be between 33 and 100 mM Nair et al, 1995) which corresponds well to a K m of 67 mM reported here for the c-Src peptide E-E-P-L-Y-W-S-F-P-A-K-K-K. In agreement with the chemical library approach we observed a strong preference for glutamic acid in position −3, but we rarely observed negatively charged residues in position −2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The related PTK c-Src strongly required glutamic acid in position −3, isoleucine, leucine or valine in position −1, tryptophan or glycine in position +1, and one of the aromatic residues phenylalanine, tryptophan or tyrosine in position +3, The resulting consensus substrate E-X-L/I-Y-W/G-X-F/W-X resembles the findings from the chemical library approach, where the best substrates for both v-Src and c-Src appeared to be -E/D-E-E-I-Y-G-E-F . The K m of the corresponding peptide A-E-E-E-I-Y-G-E-F-E-A-K-K-K was reported to be between 33 and 100 mM Nair et al, 1995) which corresponds well to a K m of 67 mM reported here for the c-Src peptide E-E-P-L-Y-W-S-F-P-A-K-K-K. In agreement with the chemical library approach we observed a strong preference for glutamic acid in position −3, but we rarely observed negatively charged residues in position −2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on peptidic substrates and homology-based molecular models suggested that about 9 to 13 residues of a peptidic substrate could presumably contact the active site cleft of the kinase domain (Knighton et al, 1991;Bossemeyer et al, 1993), but this range of amino acid may not be fully needed, as pentapeptides have been reported to be modest substrates of PTK c-Src (Nair et al, 1995). Former investigations on substrate specificity of the catalytic kinase domains utilized a limited number of peptidic and non-peptidic substrates mostly derived empirically (Pearson & Kemp, 1991;Cheng et al, 1992;Brunati et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Peptides were synthesized by the Beckman Peptide and Nucleic Acid Facility at Stanford University (Stanford, CA, USA) and labeled with fluorescein as described previously [20]. The peptide sequences were F-src (fluorescein-AEEEIYGEFEAKKKK) [21], F-PKB (fluorescein-GRPRAATFAEG) [22], PF-PKB (fluorescein-GRPRAA(T-PO 3 )FAEG), F-calc (fluorescein-DLDVPIPGRFDRRVSVAAE) [23,24], PF-calc (Fluorescein-DLDVPIPGRFDRRV(S-PO 3 ) VAAE). All peptides were amidated on the carboxy terminus.…”
Section: Reagentsmentioning
confidence: 99%
“…The agents that inhibit the enzymatic process of a PTK have been conceptually classified by Burke: (i) inhibitors preventing the binding of substrate; (ii) inhibitors preventing the binding of ATP; and (iii) inhibitors that decrease the catalytic efficiency of the enzyme by some other mechanisms [10]. Based on the motif (EEIYGEFF) discovered by Songyang et al [36], Nair et al [37] have developed a pentapeptide substrate (Ac-IYGEF) for pp60 ...... . Conceptually, pseudosubstrate-based inhibitors that compete at the substrate binding site may have a high degree of selectivity towards PTKs.…”
Section: Discussionmentioning
confidence: 99%